Respuesta :

Answer:

5

Step-by-step explanation:

-4w+7=-10w+37

+10w      +10w

=============

6w+ 7=37

     -7   -7

==========

6w=30

/6    /6

w=5

The answer is w=5


Move variable to the left side and change its sign

-4w+7=-10w+37

Move variable to the left by adding its opposite to both sides

-4w + 10w + 7 =-10w +10w+ 37

Eliminate the opposites

-4w + 10w + 7 = 37

Move constant to the right by adding its opposite to both sides

-4w + 10w + 7 - 7 = 37 -7

And Eliminate the opposites

-4w + 10w= 37-7


Collect like terms by calculating the sum or difference of their coefficients

-4w + 10w
=
(-4+10)w

Calculate the sum

6w

6w=37-7


Subtract the numbers

6w= 30

Divide both sides of the equation by 6

6w ÷ 6 = 30 ÷ 6

Any expression divided by itself equals 1

W=30÷6

30 ÷ 6 =

w=5